Transcultural Europe
XII, 315 p.
Keywords: What are the key issues facing the makers of European cultural policy in the 2lst century? How is cultural policy at the metropolitan, national and European level addressing recent developments that are complicating the cultural and social realities of contemporary Europe? This book offers an innovative assessment of these questions and aims to provoke debates about the way forward for cultural policy in Europe. Based on extensive theoretical and empirical research by an interdisplinary team of international scholars, this volume critically addresses the way in which cultural policy has evolved until now, and develops new conceptual and theoretical perspectives for re-imagining cultural change and complexity. The book offers an interesting set of studies on transcultural flows between some major European metropoles (such as Berlin, London and Paris), on the rather closed realities of other European capitals (like Rome or Ljubljana) as well as on new cultural trends emerging in cities both at the heart and at the periphery of Europe (Vienna and Belgrade). Each contribution questions the relationship between cultural diversity, cultural policy and immigration. The book thus provides new insights into the limitations of the national framework for cultural policy and into the emerging transnational dynamics in European cities.